Investigation of allergy management in primary care: Child vs. adult prescriptions - Aydın, Volkan; Kırmızı, Neriman İpek; Ataç, Ömer; Akıcı, Narin; Akıcı, Ahmet (My University, 2021)
Objective: Allergic diseases are conditions that are frequently encountered in primary care, and different drug groups can be used in their treatment. This study aimed to compare the use of drugs in allergy in children and adults applied to primary care. Methods: We analyzed prescriptions written by those who were selected by systematic sampling (n=1431) among family physicians serving in İstanbul between January 1 and December 31, 2016. Among these, single-diagnosis prescriptions containing “T78.4-allergy, unspecified” were included in the study, and the prescriptions were divided into those written to children (<18 years old) and adults (?18 years old). The demographic characteristics of the patients and drug details in the prescriptions were compared according to the groups. Results: A total of 37,042 prescriptions with a single diagnosis of allergy were identified, and 55.9% of which were for adults. Allergy diagnosis was higher in men (52.4%) among children and in females (67.7%) among adults. Antihistamines (85.3% and 83.4%, p<0.001), systemic steroids (5.4% and 1.6%, p<0.001), and inhalants (1.8% and 1.3%; p<0.001) were more likely prescribed to adults, whereas topical drugs were prescribed more in children (51.7% and 42.7%, p<0.01). Monotherapy was more preferred in children (45.8%) than in adults (41.6%, p<0.0001). Although antihistamine monotherapy was similar in these groups, topical drug monotherapy was used more in children (10.3%) than in adults (5.6%). Prescriptions with first-generation antihistamines were higher in adults (6.8%) than in children (5.4%; p<0.001). Desloratadine was the most commonly encountered drug in the prescriptions of both pediatric and adult patients (21.2% and 10.3%, respectively). Conclusion: The study revealed that antihistamines, mostly second-generation agents, are frequently preferred. Apart from the higher prescription of systemic corticosteroids for adults and topical drugs for children, it is understood that the pharmacological management of allergic conditions in primary care shows overall similarities in both age groups.
Keywords: Allergy; Family Physicians; Pediatrics; Adults; Antihistamines; Topical Drugs